(untitled) ("Journal "U". Economy. Management. Finance.", 2020)
The article is devoted to the formation and use of local budget funds, it considers the problems of revenue of the regional budget of the Orenburg region, analyzes the indicators of the consolidated budget, considers the revenue structure of the main administrated income in the Orenburg region. The main problems of forming revenue sources of the budget are also identified and recommendations aimed at increasing the revenue base are proposed.